Bioprospecção de Bacillus spp promotores de crescimento de eucalipto - Moreira, Ana Ligia de Lima (2012)
The objective of this study was to evaluate biochemical characteristics of agronomic interest in isolates of Bacillus sp., Originating from the rhizosphere of Eucalyptus and its effect on growth of seedlings of Eucalyptus urograndis. The project was conducted under laboratory and greenhouse. From the isolation of bacteria from the rhizosphere of plants originating from different municipalities in the region west of São Paulo, were obtained from 127 isolates of Bacillus spp. Tests were performed biochemical characterization of bacterial isolates on the antagonism of pathogenic fungi, production of auxin, ammonia production and enzyme activity. In the final step we evaluated the potential of the isolates for growth promotion eucalyptus seedlings and growing plants in a greenhouse for 90 days. We evaluated growth parameters of Eucalyptus aiming to select the best individual and also correlate the different variables at work. The bioprospecting protocol isolates of Bacillus sp. the soil was valid to meet rhizobacteria promising for growing Eucalyptus urograndis. Five isolates were selected as promising for action on growth of Eucalyptus urograndis. The potential antagonistic to pathogenic fungi found in isolates of rhizobacteria helpful in the initial selection of plant growth promoting rhizobacteria eucalyptus, it showed significant correlation with plant growth.